A tutorial and an application of SM130 RFID Module and Mifare contactless smart memory card - Keçecioğlu, Ö. Fatih; Şekkeli, Mustafa; Salihmuhsin, Metin (My University, 2013)
In this study, we have developed a driving circuit based on a PIC 18F4520 microcontroller to control overall operation of an RFID tagging system. Our system utilizes a SonMicro SM130 RFID transmitter/receiver module in order to read manufacturing ID of a Mifare 1K contactless smart memory card. An RF antenna is used to perform data communication between the module and the tag. A graphical LCD is utilized to prompt messages to the user as well as display information received from the module. Our system successfully worked and manufacturing ID of the Mifare 1K memory card was displayed on the screen of the graphical LCD

Bu çalışmada bir RFID barkod sisteminin çalışmasını kontrol etmek üzere PIC 18F4520 kullanılarak bir sürücü devresi tasarlanmıştır. Sistemimiz SonMicro SM130 RFID alıcı/verici modülünü kullanarak bir Mifare 1K temassız akıllı RFID barkodunun fabrika seri numarasını okuyarak ekranda göstermektedir. Alıcı/verici modülü ile barkod arasında veri alışverişini sağlamak için bir RF anten kullanılmıştır. Kullanıcıya yönelik mesajlar ve barkoddan okunan bilgilerin gösterimi için bir adet grafik LCD kullanılmıştır. Geliştirmiş olduğumuz sistem başarılı bir şekilde çalışmış ve Mifare 1K RFID barkodunun fabrika seri numarası okunarak grafik LCD ekranında gösterilmiştir.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: SM130 RFID Module; Mifare RFID Tag; PIC 18F4520 Microcontroller; SM130 RFID Modülü; Mifare RFID Barkodu; PIC 18F4520 Mikrodenetleyicisi